2017
DOI: 10.1007/s00404-017-4412-y
|View full text |Cite
|
Sign up to set email alerts
|

Maternal–fetal vitamin D receptor polymorphisms significantly associated with preterm birth

Abstract: We show association between maternal and fetal VDR genotype variants with PTB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 43 publications
2
30
1
Order By: Relevance
“…The results of this study, controlled for confounding factors, indicate the negative effect of the homozygous maternal profile for the low‐frequency CC allele in the SNP ApaI, because it is associated with a shorter duration of gestation (Rosenfeld et al, ). Similar results were obtained in a study carried out in Israel, and it was observed that the frequency of the polymorphic allele in ApaI differed between term and preterm (Rosenfeld et al, ).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The results of this study, controlled for confounding factors, indicate the negative effect of the homozygous maternal profile for the low‐frequency CC allele in the SNP ApaI, because it is associated with a shorter duration of gestation (Rosenfeld et al, ). Similar results were obtained in a study carried out in Israel, and it was observed that the frequency of the polymorphic allele in ApaI differed between term and preterm (Rosenfeld et al, ).…”
Section: Discussionmentioning
confidence: 85%
“…The results of this study, controlled for confounding factors, indicate the negative effect of the homozygous maternal profile for the low‐frequency CC allele in the SNP ApaI, because it is associated with a shorter duration of gestation (Rosenfeld et al, ). Similar results were obtained in a study carried out in Israel, and it was observed that the frequency of the polymorphic allele in ApaI differed between term and preterm (Rosenfeld et al, ). Women with the AA and CC homozygous genotypes of the ApaI SNP were found to be at increased risk for preterm deliveries compared to the heterozygote (CA) group, after adjusting for confounding factors (Manzon et al, ).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Alterations in the VDR gene can lead to important defects in gene activation that can affect calcium metabolism [10], cell proliferation [8,16], and immune function [8]. The most studied VDR gene single nucleotide variation (SNV) related to clinical outcomes are ApaI, BsmI, FokI, and TaqI [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have produced conflicting results regarding the association between VDR gene variants and prematurity [17][18][19][20][21][22]. Different allelic frequencies among the populations arise from different genetic ancestries, so the racial origins of the studied population may be responsible for the divergent results.…”
Section: Introductionmentioning
confidence: 99%